11.7k views
2 votes
Simplify the expression. (3x/y)^-3

a. 27x^3 y^3
b. 27/x^3y^3
c. y^3/27x^3
d. 27x^3/y^3

User Yochanan
by
5.3k points

1 Answer

4 votes

Answer:

y^3/(27 x^3)

Explanation:

Simplify the following:

((3 x)/y)^(-3)

((3 x)/y)^(-3) = (y/(3 x))^3:

(y/(3 x))^3

Multiply each exponent in y/(3 x) by 3:

(y^3)/((3 x)^3)

Multiply each exponent in 3 x by 3:

y^3/(3^3 x^3)

3^3 = 3×3^2:

y^3/(3×3^2 x^3)

3^2 = 9:

y^3/(3×9 x^3)

3×9 = 27:

Answer: y^3/(27 x^3)

User Jens Ingels
by
5.9k points